2008
DOI: 10.1257/jel.46.4.946
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Gregory Clark'sA Farewell to Alms: A Brief Economic History of the World

Abstract: A Farewell to Alms advances striking claims about the economic history of the world. These include (1) the preindustrial world was in a Malthusian preventive check equilibrium, (2) living standards were unchanging and above subsistence for the last 100,000 years, (3) bad institutions were not the cause of economic backwardness, (4) successful economic growth was due to the spread of “middle class” values from the elite to the rest of society for “biological” reasons, (5) workers were the big gainers in the Bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 60 publications
(59 reference statements)
0
17
0
3
Order By: Relevance
“…2 While economic historians can debate the Industrial Revolution's legacy [see Allen's (2008) review of Clark (2007), for example], some facts are clear. Perhaps most fundamentally, Riley (2001) observed that human life expectancy more than doubled in the past two hundred years (moving from about 30 to 65 years).…”
Section: Business Mattersmentioning
confidence: 99%
“…2 While economic historians can debate the Industrial Revolution's legacy [see Allen's (2008) review of Clark (2007), for example], some facts are clear. Perhaps most fundamentally, Riley (2001) observed that human life expectancy more than doubled in the past two hundred years (moving from about 30 to 65 years).…”
Section: Business Mattersmentioning
confidence: 99%
“…Allen, whose work has focused squarely on this reversal of fortune, credits the success of this region to its productive agriculture, which, he in turn attributes to its vigorous urban economy (Allen (1998), Allen (2000), Allen (2003) The mechanism I highlight in this paper operates through the differences in the property rights in land that different European regions inherited from their past as a result of the political success of different segments of the medieval societies from which they emerged. For the purposes of the argument, it helps to think of Europe at the 18 This last point is also made by Allen when he compares England and Netherlands to France and Germany on the one hand and Italy and Spain on the other (Allen (2008)). The other key feature Allen cites for success, participation in the intraeuropean trade (which preceded by a century the rise of the Atlantic trade emphasized by Acemoglu et al (2005) and is more in line with the dating of the rise of northwestern Europe) would not do either as many eastern European countries participated heavily in this trade but remained economic failures.…”
Section: Introductionmentioning
confidence: 95%
“…Clark (2007) on the other hand emphasizes the role of religion and middle class virtues of thrift and hard work. In spite of their intellectual appeal, the supporting evidence provided by these authors is often found to be unreliable (Allen, 2008).…”
Section: Culture and Developmentmentioning
confidence: 99%